RANCANGAN PEMBOBOTAN PENILAIAN KINERJA JASA KONSULTANSI DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Agung Yana, A.A. Gde; Sudarsana, Dewa Ketut; Agung, Mirah K. (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 1 Januari 2008)
The Term of Reference (TOR) is the first stage in the technical assistance life cycle and then following by tender for consultant assistane and then technical consultancion and the last stage Final Hand Over (FHO). For evaluate the consultancy services performance, technical audit need be designed. Analytical hierarchy process (AHP) will be use to designed the evaluation form. Criteria elements in life cycle technical assitence will be structured and take the weight. The comparison of eigenvalue matricts is collected from respondence which has competency. The analysis outcomes that’s the consultant asistence performance consist of to component which the document and the consultancy services with eigenvector (0.515, 0.485) which means that the document which has a more importace weight in evaluation (51,5%). Describing of document existency consist of contain of Term Of Reference/TOR, procedure of supplied consultancy agent, contract document, project organization, auction committee with eigenvector (0.379, 0.192, 0.237, 0.124, 0.068). It means the contain of the Term of Reference/TOR has the most importance weigth in evaluation (37,9%). Describing of the work of reference frame/TOR consist of background picture, purpose and intention, work scope, facility and data of the project owner, kinds and quantity report, qualification of the personal expert, the certainty of the operational consultancy agent with eigenvector (0.123, 0.127, 0.198, 0.083, 0.155, 0.202, 0.112). It means qualification of the personal expert has the most importance weigth (20,2%). Describing of the consultancy agent supplied procedure consist of announcement, participant registration, taking of auction document, clarification meeting/aanwyzing, input document and opening of bargain, evaluation of bargaining, definited winner, the announce of winner, appointed winner with eigenvector (0.080, 0.060, 0.064, 0.068, 0.186, 0.214, 0.147, 0.101, 0.081). It means the bargaining evaluation has the most importance weight. The conducting of consultancy agent consist of the expert and assistant, aspect of time and schedule, the aspect of cost, kinds of report, office instrument and equipment with eigenvector (0.394, 0.179, 0.217, 0.134, 0.076). It means the expert and assistant has the most importance weigth.
Keywords: jasa konsultansi, penilaian kinerja AHP